Mental Health of Victims of Intimate Partner Violence: Results from the National Epidemiologic Survey on Alcohol and Related Conditions - Okuda, Mayumi (2011)
OBJECTIVE: To assess the national incidence and mental health correlates of recent intimate partner violence. METHODS: Data from the Wave 2 National Epidemiologic Survey on Alcohol and Related Conditions (n=34,653) were analyzed focusing on adults who were married, recently married, or in a romantic relationship (n=25,626). Intimate partner violence (n=1,608) included minor and severe forms of violence. The main outcome measures were the prevalence of intimate partner violence and the association of intimate partner violence with new onset of Axis I disorders. RESULTS: During the past year, 5.8% of women and 5.6% of men reported being victims of intimate partner violence. New onset axis I disorders were significantly more common among intimate partner violence victims (20.9%) than non-victims (9.4%) (OR=2.55, 2.19–2.97) and were related to frequency of violent acts. CONCLUSIONS: Intimate partner violence is common and victimization, especially if recurrent, markedly increases the risk for developing several psychiatric disorders.